Role of γδ T Cells in Lung Inflammation - Born, Willi K. (Open Immunol J, 2009)
The resident population of γδ T cells in the normal lung is small but during lung inflammation, γδ T cells can increase dramatically. Histological analysis reveals diverse interactions between γδ T cells and other pulmonary leukocytes. Studies in animal models show that γδ T cells play a role in allergic lung inflammation where they can protect normal lung function, that they also are capable of resolving infection-induced pulmonary inflammation, and that they can help preventing pulmonary fibrosis. Lung inflammation threatens vital lung functions. Protection of the lung tissues and their functions during inflammation is the net-effect of opposing influences of specialized subsets of γδ T cells as well as interactions of these cells with other pulmonary leukocytes.